ARTERIAL HYPERTENSION IN YOUNG PEOPLE: EFFICACY OF SYMPATHOLYTIC THERAPY - N. N. Nikitina; A. G. Avtandilov; K. R. Petrosyan; S. L. Petrosov (Столичная издательская компания, 2015)
Aim. To evaluate the effect of imidasoline agonist, rilmenidine (Albarel), on 24-hour blood pressure (BP) profile and autonomic regulation of cardiovascular system in young patients with arterial hypertension (HT) and exogenous constitutional obesity (ECO). Material and methods. The study included 80 men aged 18-32 ( average age 20,5 years), including 34 patients with HT and normal body weight, 36 patients with HT and ECO, 10 healthy men as a control group. All hypertensive patients were treated with rilmenidine 1-2 mg daily during 12 weeks. BP 24-hour profile and heart rate variability (HRV) were estimated before and after therapy. Results. Rilmenidine monotherapy resulted in significant reduction in average 24-hour, day-time and night-time BP as well as indices of BP loading in both groups. Indices of HRV proved the initial sympathetic overdrive among hypertensive patients especially among those with ECO. This sympathetic overdrive significantly reduced after 12 weeks of therapy. Conclusion. Rilmenidine effectively controls BP and reduces sympathetic system overdrive in young hypertensive patients with ECO.